Marketing región de Lambayeque: mejorando el turismo receptivo - Pingo Jara, Roger (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Up to now, the marketing of the Lambayeque region as a tourist destination has been able to make important progress in the growth of domestic tourists flow. 40% of these tourists come from the capital, mostly they arrive in this region, mainly for business reasons. However, little progress is shown in relation to Incoming tourism, because from 100% of visitors who arrive to this touristic destination only 5% are of foreign origin.Furthermore, in 2011, from the total foreign tourists that visited the Moche Route - La Libertad region and Lambayeque region, 70% remained in the first one and only 30% visited both regions, completing the touristic circuit. The recommendations of the teachers of the Universidad del Pacífico, Universidad Esan and Centrum Católica, who have been interviewed are compared with the businessmen’s opinions in the region, showing the importance of targeting the tourism marketing strategy. Thus, it seeks to create value in different niches of the source markets, to prioritize potential tourists from brotherly countries, to link emotionally the tourist with the city, to build brands for each touristic product, to invest in highly specialized tourism and to improve significantly the clusters organization of the tourism sector in the region.We conclude that, in the region of Lambayeque, isolated efforts have been made regarding the incoming marketing, but, according to the needs, tastes and preferences of the potential tourist, this does not fulfill the international standards. This is demonstrated by the results achieved up to now—in terms of the foreign visitors’ number—. To that extent, It emphasizes the importance of the design and the implementation of a marketing plan connected with market reality.It should profit from the national brand and develop regional and local brand based on the international touristic demand-supply relation to market niches.

A la fecha, el marketing de la región de Lambayeque como destino turístico ha logrado avanzar en el crecimiento del flujo de turistas nacionales. Estos, en un 40%, provienen de la capital y, en su mayoría, arriban a esta región, principalmente, por razones de negocio. Sin embargo, poco avance se muestra en cuanto al turismo receptivo, dado que del 100% de visitantes que llegan a este destino turístico solo el 5% es de origen extranjero. Además, del total de turistas extranjeros que, en el 2011, visitaron la ruta Moche —región de La Libertad y región de Lambayeque—, el 70% se quedó en la primera y solo el 30% visitó ambas regiones, completando el circuito turístico. Las recomendaciones de los profesores entrevistados de la Universidad del Pacífico, Universidad Esan y Centrum Católica —que son comparadas con las opiniones de los empresarios de la región—, muestran la importancia de focalizar la estrategia de marketing turístico. De este modo, se busca generar valor en los diferentes nichos de los mercados emisores, priorizar los potenciales turistas de países hermanos, vincular emocionalmente al turista con la ciudad, desarrollar marcas para cada producto turístico, invertir en turismo altamente especializado y mejorar significativamente la organización de los clusters del sector turismo de la región. Se concluye que, en la región de Lambayeque, se han realizado esfuerzos aislados respecto al marketing receptivo, pero que, de acuerdo a las necesidades, gustos y preferencias del potencial turista, este no cumple con estándares internacionales. Ello se demuestra por los resultados logrados a la fecha —en cuanto al número de visitantes extranjeros—. En esa medida, destaca la importancia del diseño y de la implementación de un plan de marketing conectados con la realidad del mercado. Se debe ubicar bajo la cobertura de la marca país y desarrollar la marca regional y local basándose en la relación demanda-oferta turística internacional por nichos de mercado.
Lambayeque Region marketing: Improving Incoming Tourism
Keywords: Marketing turístico; Marca turística; Turismo receptivo; https://purl.org/pe-repo/ocde/ford#5.02.04